Impacto de secuencias con centeno y vicia en el carbono del suelo - Rojas, Julieta Mariana; Czyruk, Lorena Soledad; Roldan, Maria Florencia; Burdyn, Belen (Asociación Argentina Ciencia del Suelo, 2024)
Póster